PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Palayukan, Silvia; Rijal, Abdul; Hasyim, Sitti Hajerah (Jurnal Sains Riset, 2024)
This study aims to determine the effect of Profitability on Firm Value in the Food and Beverage Sector on the Indonesia Stock Exchange. The variables in this study are Profitability as the independent variable, and Firm Value as the dependent variable. The population in this study are companies in the Food and Beverage Sector on the Indonesia Stock Exchange from 2019 to 2021 with a total of 26 companies. Sampling was carried out using a purposive sampling technique, namely a sampling technique with certain considerations and criteria with a sample of 16 companies. The data collection technique used is documentation. Data analysis techniques using descriptive statistical analysis, simple linear regression, t test, and the coefficient of determination. Based on the results of the study that Profitability has a significant effect on Firm Value in the Food and Beverage Sector on the Indonesia Stock Exchange. Based on the results of the study that: (1) the results of the descriptive analysis show that profitability (ROA) has a maximum value of 0.74, a minimum value of 0.2, an average value of 0.2888, and a standard deviation value of 18,143, besides that the company value (PBV) has a maximum value of 57.35, a minimum value of 1.71, an average value of 11.3519 and a standard deviation value of 13.40152. (2) the results of simple linear regression analysis obtained the equation Y = 4.164 + 53.735X, (3) the results of the t-test obtained the results of a sig value of 0.001 0.05, which means the variable Profitability on Firm Value in the Food and Beverage Sector on the Indonesia Stock Exchange, (4) the coefficient of determination is 0.529 or 52.9 percent. This means that profitability has an influence on firm value of 52.9 percent while the remaining 47.1 percent is influenced by other factors.